On the Necessity of Including Joint Passive Dynamics in the Impedance Control of Robotic Legs. (17th July 2014) - Arevalo, Juan Carlos; Cestari, Manuel; Sanz-Merodio, Daniel; Garcia, Elena
Bioinspired quadruped robots are among the best robot designs for field missions over the complex terrain encountered in extraterrestrial landscapes and disaster scenarios caused by natural and human-made catastrophes, such as those caused by nuclear power plant accidents and radiological emergencies. For such applications, the performance characteristics of the robots should include high mobility, adaptability to the terrain, the ability to handle a large payload and good endurance. Nature can provide inspiration for quadruped designs that are well suited for traversing complex terrain. Horse legs are an example of a structure that has evolved to exhibit good performance characteristics. In this paper, a leg design exhibiting the key features of horse legs is briefly described. This leg is an underactuated mechanism because it has two actively driven degrees of freedom (DOFs) and one passively driven DOF. In this work, two control laws intended to be use in the stan ce phase are described: a control law that considers passive mechanism dynamics and a second law that neglects these dynamics. The performance of the two control laws is experimentally evaluated and compared. The results indicate that the first control law better achieves the control goal; however, the use of the second is not completely unjustified.